The Impact of Social Media on Academic’s Performance among Undergraduate Students in Kathmandu - Devkota, Pooja; Gurung, Neera; Bhatta, Kabita (Journal of Advanced Academic Research, 2024)
Social media has fostered a new era of partnerships and communication significantly affecting the lives of young people. The new technology has changed how we talk and has made social media, a place on the internet where everyone can connect and share with others, a big thing. On the other hand, social media has drawn in young people and students, often to the point of wasting their valuable time, energy, and money. This study aimed to evaluate the social media’s influence on academic performance of bachelor level students in Kathmandu Metropolitan City. A cross-sectional descriptive study drew the sample of 251 students by using simple random sampling technique for the selection of student in the study. Among the maximum respondents of 23-26 years male, a significant portion of the respondent, i.e. half of them believed that the social networking sites were affecting their academic performance positively and believed that it was possible to reduce negative effects of social networking sites, the use of social platforms for both academic and personal purpose. On the other hand, respondents complained about the headache, back pain, loss of concentration and memory along with unrealistic expectation and false emotions. This study summarizes that networking sites affect academic performance both positively and negatively.